Design for database access control mechanism based on blockchain - Yonggui FU; Jianming ZHU (Tongxin xuebao)
Aiming at the current problems of database access control,the thought of blockchain technology applied to database access control was proposed.The implementation mechanism of database access control based on blockchain was designed from several aspects as blockchain hierarchical structure,logical hierarchical structure of access control process,implementation principle of access control,consensus authentication principle of access control,and construction mechanism of access control blockchain system.The performance of database access control system based on blockchain was assessed.A complete framework was provided for blockchain applied in database access control.Through strengthening the authentication and supervision of visitor identity,access permission and access behavior,the database access control ability is improved effectively.